The Impact of Communication and Service Synergy on Elementary School Customer Satisfaction: A Case Study in a Private Elementary School - Gizella, Rahel; Santosa, Heru; Zulaikha, Siti (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the influence of persuasive communication and school services on customer satisfaction at XYZ Private Elementary School in Jakarta. Using a quantitative approach and survey method, this study involved 116 parents of students through a questionnaire that had been tested for validity and reliability. Data analysis was conducted using normality tests, ANOVA, Pearson correlation, and multiple regression. The results of the study indicate that persuasive communication (β = 0.345; p < 0.001) and school services (β = 0.635; p < 0.001) significantly influence customer satisfaction, with a coefficient of determination R² of 0.573. School services contributed effectively by 43.18%, which is greater than persuasive communication at 14.80%. These findings support the theory of Total Quality Management (TQM) and the concept of educational service quality, which emphasizes the importance of synergy between persuasive communication and excellent service. The practical implications of this study encourage schools to implement data-driven communication and service strategies to enhance parental loyalty. This research offers a novel contribution through an integrative approach between communication and service aspects as the foundation for holistic and sustainable management of educational customer satisfaction.